2012
DOI: 10.1103/physrevlett.109.058102
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Bilayers and Membrane Dynamics: Insight into Thickness Fluctuations

Abstract: Thickness fluctuations have long been predicted in biological membranes but never directly observed experimentally. Here, we utilize neutron spin echo spectroscopy to experimentally reveal such fluctuations in a pure, fully saturated, phosphocholine lipid bilayer system. These fluctuations appear as an excess in the dynamics of undulation fluctuations. Like the bending rigidity, the thickness fluctuations change dramatically as the lipid transition temperature is crossed, appearing to be completely suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
154
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(170 citation statements)
references
References 36 publications
15
154
1
Order By: Relevance
“…Membrane thickness fluctuations were only observable in the fluid phase of the bilayer, implying that such fluctuations are either completely suppressed in the gel phase of the membrane (19) or are slowed down beyond the temporal resolution of the NSE technique. The study also showed almost identical thickness fluctuation patterns (12) in the bilayers, regardless of the length of the lipid molecules used. This invariability in the dynamical behavior relative to lipid tail-length can be attributed to geometrical constraints caused by the minimalistic bilayer composition in this overly simplistic system, which favors uniform bilayer thickness and lateral membrane homogeneity.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Membrane thickness fluctuations were only observable in the fluid phase of the bilayer, implying that such fluctuations are either completely suppressed in the gel phase of the membrane (19) or are slowed down beyond the temporal resolution of the NSE technique. The study also showed almost identical thickness fluctuation patterns (12) in the bilayers, regardless of the length of the lipid molecules used. This invariability in the dynamical behavior relative to lipid tail-length can be attributed to geometrical constraints caused by the minimalistic bilayer composition in this overly simplistic system, which favors uniform bilayer thickness and lateral membrane homogeneity.…”
Section: Introductionmentioning
confidence: 58%
“…However, the full extent of the role of fast dynamics is still poorly understood due to the experimental difficulties in probing this time regime. Interestingly, these timescales coincide with those of collective thermal fluctuations in lipid bilayers (12,13), which starts to suggest that tuning these fluctuations is critical for medical applications requiring selective macromolecule binding. Of particular interest in this context are membrane thickness fluctuations whose dynamics are on the same timescale as conformational transitions in proteins (8) and that have been associated with other membrane functions such as pore formation (14) and passive permeation (15).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, alternative explanations of this anomaly have cited internal bilayer friction as a possible explanation (Watson and Brown 2010;Woodka et al 2012).…”
Section: Dynamicsmentioning
confidence: 93%
“…Elastic and quasielastic neutron scattering can access the pico-to nanosecond dynamics (Benedetto and Kearley 2016;Magazù et al 2008Magazù et al , 2009Magazù et al , 2010Magazù et al , 2012Bee 1988;Volino 1978). Neutron spin-echo can be used to investigate slower relaxation processes (Mezei 1972) and to probe structural fluctuations (Nagao 2009;Woodka et al 2012). Finally, smallangle neutron scattering and diffraction can be used for further structural characterization.…”
Section: Introductionmentioning
confidence: 99%